2004
DOI: 10.1073/pnas.0402293101
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive association of the proapoptotic protein Bim with Bcl-2-related proteins on mitochondria in T cells

Abstract: Apoptosis in activated T cells in vivo requires the proapoptotic Bcl-2 family member Bim. We show here that, despite its ability to bind LC8, a component of the microtubule dynein motor complex, most of the Bim in both healthy and apoptotic T cells is associated with mitochondria, not microtubules. In healthy resting T cells Bim is bound to the antiapoptotic proteins Bcl-2 and Bcl-x L. In activated T cells, levels of Bcl-2 fall, and Bim is associated more with Bcl-x L and less with Bcl-2. Our results indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
113
0
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(135 citation statements)
references
References 46 publications
21
113
0
1
Order By: Relevance
“…Hildeman et al [18] have further shown that pro-apoptotic Bim is required for activated T cells to die during clonal contraction. Although initially thought to be regulated by subcellular localization [34], Bim has recently been shown to reside in the mitochondria whether or not T cell death is induced by growth factor withdrawal [35]. We tested for Bim expression in this study and found that The MFI for Bcl-x was determined after the indicated treatments and normalized to Bcl-x levels found in CD4 + DO11.10 TCR + cells from untreated mice.…”
Section: Discussionmentioning
confidence: 92%
“…Hildeman et al [18] have further shown that pro-apoptotic Bim is required for activated T cells to die during clonal contraction. Although initially thought to be regulated by subcellular localization [34], Bim has recently been shown to reside in the mitochondria whether or not T cell death is induced by growth factor withdrawal [35]. We tested for Bim expression in this study and found that The MFI for Bcl-x was determined after the indicated treatments and normalized to Bcl-x levels found in CD4 + DO11.10 TCR + cells from untreated mice.…”
Section: Discussionmentioning
confidence: 92%
“…In these cells, Bim is probably kept inactive by sequestration to the dynein motor complex on microtubules and activated by its release through an unknown mechanism (Puthalakath et al, 1999). In primary T cells, Bim was reported to be already localized to mitochondria in the absence of apoptosis, and a drop in Bcl-2 and Bcl-x L levels might in this case be the trigger to induce apoptosis (Zhu et al, 2004). Because the activation mechanism of Bim is not understood more clearly, it is difficult to say which stimuli might activate Bim.…”
Section: Discussionmentioning
confidence: 99%
“…For example, most of the Bim is associated with Bcl-2 and Bcl-x L at the mitochondria rather than at the microtubules in both healthy and apoptotic T cells. 42 The core DLC1-binding region maps to the sequence DKSTQTP (51-57 aa in Bim L and 111-117 aa in Bim EL ) found in exon 4 of Bim L and Bim EL . Certain cellular stresses promote the release of Bim L and Bim EL from microtubules, 9 raising the possibility that this is a dynamic process regulated by stress-induced signalling pathways.…”
Section: Phosphorylation Of Bim L By Jnk Regulates Its Interaction Wimentioning
confidence: 99%